Molecular pathways in experimental glaucoma models - Bugara, Klaudia; Pacwa, Anna; Smedowski, Adrian (Frontiers in Neuroscience, 2024)
Glaucoma is a complex and progressive disease that primarily affects the optic nerve axons, leading to irreversible vision loss. Although the exact molecular mechanisms underlying glaucoma pathogenesis are not fully understood, it is believed that except increased intraocular pressure, a combination of genetic and environmental factors play a role in the development of the disease. Animal models have been widely used in the study of glaucoma, allowing researchers to better understand the underlying mechanisms of the disease and test potential treatments. Several molecular pathways have been implicated in the pathogenesis of glaucoma, including oxidative stress, inflammation, and excitotoxic-induced neurodegeneration. This review summarizes the most important knowledge about molecular mechanisms involved in the glaucoma development. Although much research has been done to better understand the molecular mechanisms underlying this disease, there is still much to be learned to develop effective treatments and prevent vision loss in those affected by glaucoma.